Animated Company Profile and Product Procedures Multimedia-Based PT. BPR Prasta - Ketut Gus Oka Ciptahadi; I Kadek Sudirga Putra (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2025)
Bank Perekonomian Rakyat Balaguna Prasta (BPR PRASTA) was established on January 3, 1994, by Anak Agung Oka Wisnu, S.E., a private entrepreneur from Klungkung and a former Branch Manager of a well-known Private National Commercial Bank at the time. With the rapid advancement of information technology, PT. BPR Prasta has utilized the sophistication of information technology to facilitate the socialization of the institution's profile and services, such as Prasta Aman, BPR Prasta Credit, Arisan Prasta, and Taplus Pendidikan. Based on an interview conducted, it was found that PT. BPR Prasta still uses written text or images to explain its products and company profile. Therefore, the institution hopes to provide socialization to customers through an offline application that presents an animated company profile and product instructions. Based on the results of Black Box Testing in terms of functionality, the application is working well. Additionally, the questionnaire results, after being summed, averaged, weighted, and multiplied by the number of questions, produced a score of 76.1%, which is categorized as good.